2004
DOI: 10.1111/j.1469-0691.2004.00878.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of an outbreak of methicillin-resistant Staphylococcus aureus with reduced susceptibility to glycopeptides in a French hospital

Abstract: A B S T R A C TStaphylococcus aureus isolates were screened for reduced susceptibility to glycopeptides with an initial glycopeptide agar screening test, followed by confirmation of the strains thus identified by two Etest strip techniques and population analysis. This procedure detected 48 methicillin-resistant S. aureus (MRSA) isolates with reduced susceptibility to glycopeptides from 24 patients among 883 MRSA isolates tested. The dissemination of a single clone was confirmed by pulsedfield gel electrophore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…The prevalence of VISA or hVISA amongst MRSA isolates ranged from 0.1% (hVISA) and 0.3% (VISA) in Belgium [24] to 11% (VISA) in France and 18% in Turkey (hVISA) [25,26]. Furthermore, an outbreak due to VISA in a French hospital has been reported [27]. Our finding that all of the 21 patients with VISA had the same PFGE type (pulsotype A) suggests that clonal spreads of VISA have occurred.…”
Section: Discussionmentioning
confidence: 69%
“…The prevalence of VISA or hVISA amongst MRSA isolates ranged from 0.1% (hVISA) and 0.3% (VISA) in Belgium [24] to 11% (VISA) in France and 18% in Turkey (hVISA) [25,26]. Furthermore, an outbreak due to VISA in a French hospital has been reported [27]. Our finding that all of the 21 patients with VISA had the same PFGE type (pulsotype A) suggests that clonal spreads of VISA have occurred.…”
Section: Discussionmentioning
confidence: 69%
“…The reported prevalence of h‐GISA isolates ranges widely from one study to another, but was similarly low (<1%) in large surveys conducted in the UK, Italy, USA and Korea [16–19]. In contrast, a higher prevalence was observed among MRSA isolates analysed in Japan (5–22%), Germany (2–14%), The Netherlands (7.6%) and France (20%) [7,13,20,21], although other studies in France have reported lower incidences of h‐GISA (0.6–5%) [22,23]. However, such differences may be more apparent than real because of marked differences in the study design and laboratory methods used for screening and confirming the hetero‐resistance phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…In other cases, a nosocomial spread of hVISA or VISA has been suggested, with a number of outbreaks reported, mostly in France (64,105,190,253). An outbreak reported by de Lassence et al was described as 21 patients in a French ICU who had isolates of S. aureus with reduced glycopeptide susceptibility (64).…”
Section: Global Epidemiology and Associated Features Of Hvisa And Visamentioning
confidence: 99%